Tracer Study of Teacher Education Graduates of Western Philippines University - Puerto Princesa Campus: Basis for Curriculum Review and Revision - Pentang, Jupeth Toriano; Perez, David R.; Cuanan, Katherine H.; Recla, Mailyn B.; Dacanay, Romelyn T.; Bober, Rastanura M.; dela Cruz, Cheche E.; Egger, Susana P.; Herrera, Ruth L.; Illescas, Carolyn M.; Salmo, Josephine M.; Bucad, Jr., , Manuel L.; Agasa, Joann V.; Abaca, Nur-aina A. (Future Science / FSH-PH Publications, 2022)
Graduates' employability indicates the excellent education and relevant preparation they obtained from their respective degrees. Tracer studies have enabled higher education institutions to profile their graduates while also reflecting on the quality of education they provide. With the foregoing, a tracer study determined the demographic and academic profile of teacher education graduates from 2017 to 2020 in a state university in the West Philippines. It also ascertained the advanced studies they attended after college, their employment data, the relevance of college preparation with their current employment, difficulties they encountered while securing employment and in their present job, and recommendations to strengthen the teacher education program. The study utilized a descriptive survey research design with 80 non-random samples chosen based on availability. The survey was based on the Philippine Commission on Higher Education with modifications elucidated from previous studies. Results showed that graduates took the teacher education program with a strong passion for the teaching profession. More graduates received honors and awards, passed the licensure examinations for teachers, attended advanced studies for professional development, and are employable. Besides, the graduates’ college preparation is relevant to their current employment. Further, difficulties and problems encountered and recommendations to strengthen the teacher education program were noted. These findings may serve as a baseline for curriculum review and give suggestions for future tracer studies.